Upaya Pencegahan Stunting Melalui Program Pemberian Makan Tambahan (PMT) di Desa Sukamulya - Pina Maelani Putri; Azfi Azfiyani; Elnaeni Badzlina; Hilma Nanda Musyafa; Putri Amanah; Sherina Lidya Hakim; Vonny Viviani; Aulia Putri Salsabila; Fikfik Taufik (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
Stunting, a significant global health concern, is a condition where children suffer from impaired growth and development due to poor nutrition. This study evaluates the "Pemberian Makan Tambahan" (PMT) program implemented in Sukamulya Village, Indonesia, aimed at reducing stunting. The research involves collaboration between Universitas Muhammadiyah Bandung, BKKBN, and community stakeholders, focusing on providing supplementary food to children under five. The study utilized preparation implementation, monitoring, recording, and reporting. The results indicated an increase community awareness and child nutrition outcomes, emphasizing the effectiveness of targeted nutritional interventions in preventing stunting.